Recent Advances in Multifunctional Mechanical–Chemical Superhydrophobic Materials - Luo, Qinghua; Peng, Jiao; Chen, Xiaoyu; Zhang, Hui; Deng, Xia; Jin, Shiwei; Zhu, Hai (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, biology-inspired superhydrophobic technology has attracted extensive attention and has been widely used in self-cleaning, anti-icing, oil-water separation and other fields. However, the poor durability restricts its application in practice, so it is urgent to systematically summarize it so that scientists can guide the future development of this field. Here, in this review, we first elucidated five kinds of typical superhydrophobic models, namely, Young's equation, Wenzel, Cassie-Baxter, Wenzel-Cassie, “Lotus”, “Gecko” models. Then, we summarized the improvement in mechanical stability and chemical stability of superhydrophobic surface. Later, the durability test methods such as mechanical test methods and chemical test methods are discussed. Afterwards, we displayed the applications of multifunctional mechanical-chemical superhydrophobic materials, namely anti-fogging, self-cleaning, oil-water separation, anti-bacterial, membrane distillation, battery, anti-icing, etc. Finally, the outlook and challenge of mechanical-chemical superhydrophobic materials are highlighted.